Hemodynamic parameters distribution of upstream, stenosis center, and downstream sides of plaques in carotid artery with different stenosis: a MRI and CFD study. (March 2015) - Sui, Binbin; Gao, Peiyi; Lin, Yan; Jing, Lina; Sun, Shengjun; Qin, Haiqiang
Background: Histopathological studies have shown significant differences in plaque components and surface conditions between upstream and downstream of the stenosis. It can be deduced that the flow status near the plaques is different from the flow status at the upstream side, stenosis center, or downstream side of the plaque. Purpose: To study the hemodynamic parameter distribution in different locations near atherosclerotic plaques in the carotid arteries with different stenosis degrees. Material and Methods: Eleven patients were recruited in this study. CE-MRA was performed to obtain the carotid three-dimensional surface data and the stenosis degrees were calculated. The hemodynamic parameters including wall shear stress (WSS), pressure, and velocity near the plaques were obtained by computational fluid dynamic (CFD) method. Local hemodynamics parameters were analyzed and compared between different stenosis degree groups, and between upstream, stenosis center, and downstream sides of plaques. Relative ratio of velocity, WSS, and pressure values in different locations was calculated and compared. Results: Fourteen carotid arteries (with 4 mild, 6 moderate, and 4 severe stenosis) were analyzed. Significant differences were found in Pressure max ( P  = 0.025), Pressure mean ( P  = 0.020), and Pressure min ( P  = 0.026) between three stenosis groups. It showed significant differences in Vmin ( P  < 0.001) and WSSmin ( P  < 0.001) between three different locations. It showed upstream to downstream ratio of WSSmax ( P  = 0.034) and WSSmean value ( P  = 0.042) was significantly different between mild and moderate/severe groups. Significant differences were found in upstream to stenosis center ratio of Pressure max value ( P  = 0.018), Pressure mean value ( P  = 0.029), and Pressure min value ( P  = 0.026), as well as in stenosis center to downstream ratio of Pressure min value ( P  = 0.042). Conclusion: Velocity, WSS, pressure, and relative ratio of these parameters have certain trends in distribution around the plaques in the carotid arteries.